N‐Aroyl‐N′‐(1‐Naphthyl)‐N′′‐aryl guanidines as a New Entry to Urease Inhibitors: Synthesis, Kinetic Mechanism, Molecular Docking and MD Simulation Studies. Issue 15 (14th April 2023) - Tahira, Sarwat; Saeed, Aamer; Farid, Aftab; Channar, Pervaiz Ali; Tehzeeb, Arfa; Abbas, Qamar; Abdalla, Mohnad
Abstract: A series of novel guanidines (6 a –j ) was synthesized from corresponding thioureas using catalytic mercuric chloride in DMF. The synthesized compounds were characterized by spectroscopic techniques and appraised for Jack Bean Urease (JBU) inhibition. All compounds (6 a –j ) exhibited strong potential against JBU whilst compound 6 b (IC50 =0.0155±0.00087 μM) and 6 e (IC50 =0.0091±0.00036 μM) displayed excellent urease inhibition compared to thiourea (IC50 =18.27 μM) used as reference. The kinetic mechanism analyzed by Lineweaver‐Burk plots revealed that 6 b is a mixed‐type inhibitor while 6 e is a non‐competitive inhibitor. Thus, compounds 6 e and 6 b can serve as a structural model for the designing of super‐effective urease inhibitors. Binding affinity and interaction of N ‐aryl guanidine analogs were evaluated through molecular docking studies. To evaluate the residual flexibility of receptor through MD simulation, RMSD and RMSF graphs were evaluated to determine the protein structural behavior. It is implied that compound 6 e can serve as a novel molecular template to medicinal chemists for designing more potent urease inhibitors. Abstract : A series of novel guanidines (6 a –j) was synthesized from corresponding thioureas and appraised for Jack Bean Urease (JBU) inhibition. Compound 6 b (IC50 =0.0155±0.00087 μM) disclosed several folds better inhibition compared to the standard thiourea (IC50 =18. 27 μM).